Diagnostic value of Breast Specific Gamma Imaging with semiquantitative index (T/N) in Breast Cancer Diagnosis - Mallik, Dipendra Kumar; Hong, Wei Zhang; Zhu, Wei; Wei, Ge Yang; Shen, Lei; Guang, Fu Hu; Sapkota, Ganga (Nepalese Journal of Cancer, 2018)
Objective: The study in this part was to evaluate the diagnostic value of Breast Specific Gamma Imaging (BSGI) by semi-quantitative method for detection of breast cancer. Methods: 400 patients with indeterminate breast tumors that underwent BSGI were enrolled in this study. All included lesions were confirmed by postoperative pathology. BSGI evaluation was based on the visual interpretation and semi-quantitative parameters of the higher tumor to non-lesion (T/N) value of CC and MLO. Compared with pathological results, the optimal visual analysis and the value of T/N were calculated through ROC curve analysis. Independent t-test and Pearson linear correlation were applied for statistical analysis. Results: Tumor to non-lesion (T/N) ratio was available for 279 out of 400 patients. This population comprised 203 patients with malignant and 74 patients with benign lesion. ROC analysis showed critical value of T/N= 1.91, AUC is 0.83 (standard error=0.014, 95% confidence interval); BSGI sensitivity is 83.71% and specificity is 76%. T/N ratio for invasive and non-invasive cancers are 2.70± 0.88, and 2.09±0.44 respectively; the difference between two have statistical significance (t=3.32, P=0.001). Infiltrating ductal carcinoma (IDC) grade I, grade II, and grade III have T/N ratio of 2.33±0.94, 2.38±0.80, 2.89±0.89 respectively. The T/N differences between grade I and grade II have no statistical significance (t=0.12, P=0.89). The T/N differences between grade I and grade III have no statistical significance (t=1.56, P=0.12). The T/N differences between grade II and grade III have statistical significance (t=3.69, P<0.001). T/N value for tumor size <1cm and >1cm were 1.97±0.79 and 2.46±0.88 respectively; the difference between two have statistical significance (t=3.27, P=0.001). Conclusion: The semi-quantitative index of T/N correlates with clinico-pathological characteristics of tumor like: size, grade, and invasiveness of breast cancer, and at certain level can be helpful to determine patient’s prognosis.